Fruit, vegetable consumption and blood pressure in healthy adolescents: A longitudinal analysis from the LabMed study - Rosário, Rafaela (2018)
Background and aims: The associations between fruit and vegetable consumption and high blood pressure among adults are well studied. Nonetheless, data on the influence of a low consumption of fruit and vegetables on cardiovascular disease risk, particularly blood pressure, among healthy adolescents are scarce. Therefore, we aim to analyse the associations between fruit and/or vegetable intake and blood pressure over a two-year period in healthy adolescents.Methods and results: As part of a cohort, 606 adolescents from the LabMed Physical Activity study were evaluated in 2011 (baseline) and 2013 (follow-up). Blood pressure was measured according to standardized procedures and fruit and vegetable consumption was assessed with a food frequency questionnaire. Anthropometric variables, socioeconomic status, pubertal stage and lifestyle determinants were gathered and used as confounders. Prospective associations between fruit and/or vegetable intake and blood pressure were examined using generalized linear models. Girls who consumed more fruit at baseline had a significant decrease in diastolic blood pressure at follow-up [unstandardized beta: -0.005 mmHg (95% CI: -0.01; -0.0002) (p = 0.038)].Conclusion: In apparently healthy adolescents, fruit intake may already start to have an effect in blood pressure. Girls who consumed more fruit exhibited lower levels of diastolic blood pressure. (C) 2018 The Italian Society of Diabetology, the Italian Society for the Study of Atherosclerosis, the Italian Society of Human Nutrition, and the Department of Clinical Medicine and Surgery, Federico II University. Published by Elsevier B.V. All rights reserved.